A Campylobacter jejuni homolog of the LcrD/FlbF family of proteins is necessary for flagellar biogenesis. - Miller, S (1993)
A Campylobacter jejuni homolog of the lcrD/flbF family of genes was cloned and sequenced. The nucleotide sequence of the gene, called flbA, predicted a protein of 78,864 Da, with significant homology to a group of related proteins including the Yersinia pestis LcrD, Salmonella typhimurium InvA, and Caulobacter crescentus FlbF proteins. The greatest homology was seen with the C. crescentus FlbF protein, with an overall amino acid sequence homology of 57%. An insertion mutation in the C. jejuni 81-176 flbA gene was constructed. The resultant strain did not synthesize flagellin and was nonmotile.